The metaphysics of transcendental subjectivity: Descartes, Kant and W. Sellars - Evans, Joseph Claude (Amsterdam Verlag B. R. Grüner, 1984)
The general topic of this book is the metaphysics of the subject in Kantian transcendental philosophy. A critical appreciation of Kant's achievements requires that we be able to view Kant's positions as transformations of pre-Kantian philosophy, and that we understand the ways in which contemporary philosophy changes the letter of Kantian thought in order to be true to its spirit in a new philosophical horizon. Descartes is important in two respects. One the one hand, he institutes a philosophical movement which can be said to culminate in Kant; on the other hand, Descartes is one of the major opponents against whom Kant argues in establishing his own position. In either case, the Cartesian cogito is a central concern. Wilfred Sellars restates and transforms Kantian positions in the context of contemporary philosophy after the "linguistic turn", using the Platonic metaphor that thought is similar to discourse.